Transformasi Media Pembelajaran Di Masa Pandemi Covid-19 - Susilawati, Susilawati; Yasir, Muhamad (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2021)
The purpose of this community service activity is to provide information to the people of the village of Choblong Cibeureum Cisarua Bogor about the variety of learning media that can be used during distance learning activities (learning from home). The target of community service is the community in the area of ​​RT.03 RW.010 Cibeureum Cisarua, Bogor. Partner problems can be resolved through three stages: preparation, implementation, and evaluation. Preparations were carried out by conducting a preliminary survey to see conditions in the field regarding distance learning during the Covid-19 pandemic. The implementation is carried out by counseling, using the lecture method, namely presentation techniques, followed by question and answer discussions and exercises to open links to free online learning providers as interesting online-based learning media. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of activity. The results of the training activities showed a success rate with an indication of a positive response from the participants, and most (75%) of the participants had understood how to open a link to an online learning provider.